Sistem Informasi Akuntansi Bank Sekolah Menggunakan Metode Cash Basis - Tantik Sumarlin; Nining Fitriani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Bank is a production unit under the organizational structure of a business center in a school. This bank provides services in the form of savings deposit transactions and savings withdrawals. Bank customers are all students in grades ten to twelve along with teachers and employees. The information system required is a web-based school bank information system using the cash basis method so that it can assist in operational activities ranging from recording daily transactions to reporting. The research was conducted using the Research and Development (R&D) method, UML (Unified Modeling Language) modeling, the PHP (Hypertext Preprocessor) programming language with the MySQL MariaDB database. The School Bank Accounting Information System is expected to be able to solve the problems that occur in the school bank.